Compressive effect of the magnetic field on the positron range in commonly used positron emitters simulated using Geant4. Issue 11 (November 2017) - Li, Chong; Cao, Xingzhong; Liu, Fuyan; Tang, Haohui; Zhang, Zhiming; Wang, Baoyi; Wei, Long
Abstract. The compressive effect of a magnetic field on the positron range from commonly used positron emitters in PET (Positron Emission Tomography) was simulated using the Geant4 toolkit with H2 O as the environmental material. The compression of the positron range, which was different in the directions parallel and perpendicular to the magnetic field, showed finite final variation of relative change rateversus the magnetic field. The variation greatly depended on the positron-emission energy spectrum in the same medium. Furthermore, the volume of the positron annihilation point was dramatically compressed as the magnetic field was set in the range of 3-6T. It was more prominent for82 Rb, which is generally used as a positron source in PET technology.